Accounting conservatism and life cycle stages in brazilian credit unions - Stüpp, Diego Rafael; Flach, Leonardo; Lerner, Arthur Frederico; Conesa, Isabel Martínez (REVISTA AMBIENTE CONTÁBIL - Universidade Federal do Rio Grande do Norte - ISSN 2176-9036, 2026)
Purpose: This study analyzes how the different stages of the life cycle influence accounting conservatism in Brazilian credit unions, filling a research gap regarding the relationship between organizational maturity and financial reporting quality in non-profit entities. Methodology: The research employed panel data regression modeling for a sample of 615 Brazilian credit unions from 2017 to 2023. The cooperatives were grouped into life cycle clusters based on the models of Vasylieva and Chmutova (2015) and Maia (2022). Accounting conservatism was measured using the models of Ball and Shivakumar (2005) and Beatty and Liao (2011). Results: The panel model results demonstrate that life cycle stages have explanatory power over the accounting conservatism of Brazilian credit unions, confirming the proposed hypothesis. Study Contributions: The research extends the application of life cycle theory to the credit union sector, demonstrating that accounting conservatism varies across stages. This provides novel evidence for the Brazilian context and emerging markets.